PENGARUH PENGGUNAAN APLIKASI MUSLIM PRO SEBAGAI MEDIA PEMBELAJARAN TERHADAP PEMAHAMAN HUKUM TAJWID SISWA DI MTSS NURUL FALAH,SOLOK SELATAN - Wira Restia Dinda; Arman Husni (CV. ADIBA AISHA AMIRA, 2023)
Using the pro Muslim application in learning tajwid science material will make it easier for students to learn, not get bored in memorizing the Qur'an and can prepare for life in the 5.0 era, students are expected to be able to use gedged effectively and efficiently according to the needs of students. This type of research used quantitative research methods using a quasi-experimental approach, with a Quasi Nonequivalent Control Group design. Researchers provide treatment and examine changes or differences from the treatment that has been given. Quasi-experimental research has the goal of finding out the variables that will involve the control class and the experimental class. Decision making significant value <0.05 indicates a significant difference between the initial variable and the final variable. The sig value has a value of 0.000 indicating that there is a significant effect on the difference in the treatment given to each variable. So it can be concluded that